1994
DOI: 10.1128/mcb.14.5.3041
|View full text |Cite
|
Sign up to set email alerts
|

DNA-binding-defective mutants of the Epstein-Barr virus lytic switch activator Zta transactivate with altered specificities.

Abstract: The Epstein-Barr virus BRLF1 and BZLF1 genes are the first viral genes transcribed upon induction of the viral lytic cycle. The protein products of both genes (referred to here as Rta and Zta, respectively) activate expression of other viral genes, thereby initiating the lytic cascade. Among the viral antigens expressed upon induction of the lytic cycle, however, Zta is unique in its ability to Epstein-Barr virus (EBV) is a lymphotropic human herpesvirus that latently infects B lymphocytes, resulting in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 45 publications
0
31
1
Order By: Relevance
“…Francis and colleagues have identified a single amino acid substitution mutation in Zta (S186A) that abrogates the transcription activation of latent viral chromosomes but has no detectable effect on the transcription activation of transiently transfected reporter plasmids (32). Additionally, a DNA binding defective mutant of Zta could stimulate transcription from a subset of viral promoters, suggesting Zta activates transcription at some promoters by a DNA binding independent mechanism (31). Together, these observations indicate that Zta can regulate transcription by diverse mechanisms, and modulation of CBP HAT activity, as we have described here, may be an important component of Zta-mediated transcription activation.…”
Section: Discussionmentioning
confidence: 54%
“…Francis and colleagues have identified a single amino acid substitution mutation in Zta (S186A) that abrogates the transcription activation of latent viral chromosomes but has no detectable effect on the transcription activation of transiently transfected reporter plasmids (32). Additionally, a DNA binding defective mutant of Zta could stimulate transcription from a subset of viral promoters, suggesting Zta activates transcription at some promoters by a DNA binding independent mechanism (31). Together, these observations indicate that Zta can regulate transcription by diverse mechanisms, and modulation of CBP HAT activity, as we have described here, may be an important component of Zta-mediated transcription activation.…”
Section: Discussionmentioning
confidence: 54%
“…BZLF1 has been previously described as a member of the bZip family (2, 5, 7, 13-15, 20, 25, 28). In support of this conjecture, it has been shown that BZLF1 contains adjacent DNA-binding (approximately residues 175 to 195) and multimerization (approximately residues 196 to 245) regions, and the protein interacts with specific DNA sequence elements (2,5,8,13,15,20,28,30) as a multimer (2,8,15). By analogy with other members of the bZip family, multimerization has been assumed to occur through the folding of a coiled-coil interface within this region (i.e., residues 196 to 245).…”
mentioning
confidence: 81%
“…7C), indicating binding of Zta to the IL-8 promoter in vivo. We also examined the effects of two DNA-binding-defective Zta mutants, Zdbm1 and Zdbm2, which contain mutations within the DNA-binding domain (28). The two Zta mutants were not recruited to the IL-8 promoter in a ChIP assay (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The simian virus 40 promoter-driven, Zta-or Rta-expressing plasmids have been described in our previous study (13). Plasmids expressing Zta with deletion of amino acids 27 to 53 (d27/53) or amino acids 52 to 78 (d52/78), or with mutations within the DNA-binding domain, have also been used previously (27,28). A series of pIL-8-Luc, the reporter plasmids with deletion or site-directed mutation of the IL-8 promoter, were constructed by inserting PCRamplified IL-8 promoter fragments into pGL2-basic vector (Promega) at the 5Ј KpnI site and the 3Ј NheI site.…”
Section: Methodsmentioning
confidence: 99%